Guidance Note for Surveillance Under Article IV Consultations. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2022)
This Guidance Note provides guidance to country teams for surveillance under Article IV consultations. It supersedes the 2015 Guidance Note and its supplement. Fund surveillance continuously adapts to the evolving economic and financial landscape. The 2021 Comprehensive Surveillance Review (CSR) identified priorities for Fund surveillance, both in terms of content and modalities. This Guidance Note covers: Scope and requirements: The note lays out the coverage of, and formal requirements for, Article IV consultations and staff reports. It also outlines best practices aimed at enhancing the traction of Fund analysis and policy advice. Priorities and focus. The note reflects the four surveillance priorities identified in the CSR: (i) confronting risks and uncertainties, (ii) preempting and mitigating spillovers, (iii) ensuring economic sustainability, and (iv) adopting a more unified approach to policy advice. The note also provides guidance on sharpening the focus and selectivity of Article IV staff reports. Policies. The note discusses the content of surveillance in the areas of fiscal policy, macrofinancial analysis and financial policies, monetary policy, external sector policies, and macrostructural policies. Applications. The note considers several applications of such policies, such as with respect to the Integrated Policy Framework, climate change, and gender. Process and procedures. The note describes the Article IV consultation cycle and process, lays out drafting and publication guidelines for staff reports, and covers the treatment of confidential information.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Investment; Long-Term Capital Movements; Monetary Policy; Political Economy